The present state of PST/PTB reconstruction: can we even write a fable in Proto-Lolo-Burmese? - Matisoff, James A. (2024)
How much can we really recover from the past history of languages? What do we mean when we claim to have "reconstructed a proto-language"? In sober moments, all historical linguists have to admit that a "proto-language" is at best only a pale reflection of a real living language. Often all that can be salvaged is the proto-phonemic system, along with a collection of mostly unrelated individual lexical items. If we are lucky, and work in a family with anciently attested texts in several languages, we can also achieve some understanding of the proto-grammar, especially if the languages are rich in morphology. In these respects, Indo-Europeanists have been much better off than Sino-Tibetanists, to the point where the 19th century scholar August Schleicher once dared to compose a fable in Proto-Indo-European.'